1999
DOI: 10.1128/jvi.73.11.9256-9265.1999
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Stability of Foamy Viruses: Long-Term Study in an African Green Monkey Population

Abstract: The genetic variability of the envelope surface domain (SU) of simian foamy virus (FV) of African green monkeys was studied. To assess the interindividual diversity of FV, isolates were obtained from 19 animals living together in a monkey house. The monkeys had been imported from Kenya prior to being placed in long-term housing in the research institute. In addition, a simian FV isolate and proviral DNA were obtained from an animal caretaker infected in this setting. DNA of the complete SU (1779 to 1793 bp) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 48 publications
0
30
1
Order By: Relevance
“…Second, we observed that amino acid changes in apes and OWM SFV sequences are located at positions found to have a minor impact on recognition by plasma samples. Third, we observed a major exception, i.e., the W 108 R change in some Chlorocebus SFV strains (22). Systematic testing of plasma samples revealed rare recognition of peptide cae_agm22 by samples from two gorilla SFV-infected individuals, leading to modification of the putative binding motif to 96 NKDIQVLGPVID/VW/RNV 110 .…”
Section: Discussionmentioning
confidence: 85%
“…Second, we observed that amino acid changes in apes and OWM SFV sequences are located at positions found to have a minor impact on recognition by plasma samples. Third, we observed a major exception, i.e., the W 108 R change in some Chlorocebus SFV strains (22). Systematic testing of plasma samples revealed rare recognition of peptide cae_agm22 by samples from two gorilla SFV-infected individuals, leading to modification of the putative binding motif to 96 NKDIQVLGPVID/VW/RNV 110 .…”
Section: Discussionmentioning
confidence: 85%
“…SFV genomes display a high evolutionary conservation among all the species infected and SFV genetic variability within one infected animal is very low over time (<1% variation over 13 years) [28]. This genetic stability might be explained by the long co-evolution with their host [29 ] and their subsequent efficient adaptation.…”
Section: Sfv Genetic Stabilitymentioning
confidence: 99%
“…The prevalence of FVs in naturally infected animals is generally high, but can vary widely according to species and environmental conditions. Several epidemiological studies indicated that, among captive NHP populations (Blewett et al, 2000;Calattini et al, 2004;Hussain et al, 2003;Schweizer et al, 1999Schweizer et al, , 1995, but also in free-range colonies (Calattini et al, 2006c;Mouinga-Ondeme et al, 2010) and in the wild (Jones-Engel et al, 2005;Leendertz et al, 2010;Liu et al, 2008), SFV seroprevalence can reach up to 75-100% in adults, but is generally much lower in infants and juveniles (Liu et al, 2008). SFV virions are present at a high concentration in the saliva of infected NHPs (from 10 4 to 10 9 FV RNA copies/10 4 cells equivalent).…”
Section: Historymentioning
confidence: 99%